Synthesis of constructive-technological decisions of regulation of working capacitance of cables of industrial networks - Bezprozvannych, G.V.; Kostiukov, I.A.; Pushkar, O.A. (Electrical Engineering & Electromechanics, 2021)
Introduction. Over the past 10 years, the number of industrial networks has more than doubled. At the physical level, all industrial technology networks are based on twisted pair. Purpose. Synthesis of constructive-technological decisions of regulation of electric capacitance of the insulated conductor at a stage of manufacturing of twisted pair of cables of industrial networks. Methodology. The method of secondary charges to determine the capacitance of the insulated conductor by varying the thickness of the solid and foamed polyethylene insulation. Practical value. Effective regulation is provided on the basis of the obtained dependencies of the effective dielectric constant, the tangent of the dielectric loss angle and the capacitance of the insulated conductor on the degree of foaming and the thickness of the protective film of two-layer insulation. At a degree of porosity of 40 %, the dielectric constant decreases by 25 %, the tangent of the dielectric loss angle – by 33 %, the electrical capacitance of the insulated conductor – by 20 %.